Pengaruh Proporsi Angkak (Red Mold Rice) Terhadap Karakteristik Fisikokimia dan Organoleptik Sosis Ikan Nila - Qois, Jihan Lisa Puspitasari; Sukardi, Sukardi; Anggriani, Rista (Universitas Muhammadiyah Malang, 2023)
The boiling process causes the color of the meat in the sausage to fade, so efforts are needed to improve the color of tilapia sausage using natural dyes that are safe for consumption. The addition of angkak was chosen for food coloring so that it can affect the level of consumer acceptance. The purpose of this study was to determine the effect of the addition of angkak proportion on the physicochemical characteristics and organoleptic score of tilapia sausage produced. The treatment added is the proportion of angkak which consists of 6 concentrations, namely 0%, 0.5%, 1%, 1.5%, 2% and 2.5% (% calculated from the total weight of tilapia and tapioca flour). The test parameters were water content, fat content, protein content, antioxidant activity, color intensity, hardness, and organoleptic test of taste, aroma, color, and texture. The best treatment was tilapia sausage with the addition of 1.5% angkak proportion (A3) with an average moisture content of 61.85%; protein 15.87%; fat 15.35%; antioxidant activity 40.49%; texture hardness 31.59 N; color intensity: brightness (L) 44.85; redness (a) 23.37; yellowness (b) 13.05; organoleptic: color 4.23 (red); taste 3.86 (moderately savory); aroma 2.63 (not fishy); texture 4.43 (chewy). Keywords: tilapia sausage, angkak